Autonomous jumping robot with regulable trajectory and flexible feet. (October 2014) - Chai, H; Ge, WJ; Yang, F; Yang, GM
In this paper, a prototype of jumping robot with flexible feet is proposed to surmount obstacle efficiently. A six-bar adjustable mechanism for regulating jumping height and distance as well as a self-righting mechanism for uprighting after falling down are presented. The jumping height, jumping distance and energy conversion efficiency (ECE) are analyzed and tested, respectively, through dynamics modeling and jumping experiments. Taking advantage of flexible feet whose parameters are optimally designed, both the ground impulse acting on the robot and external kinetic energy relating to the movement of robot's center of mass increase, so the performance of jumping height and distance as well as ECE of the robot with flexible feet is better than that of the one without flexible feet. By reducing leg mass and take-off angle as well as increasing stored energy, the external kinetic energy is enlarged, and ECE of the robot with flexible feet could be further improved. Meanwhile, simulation results show that the existing jumping robots which adopt four- or six-bar jumping mechanism are capable of enhancing jumping height and distance as well as ECE by exploiting flexible feet.